Dalfampridine: Review of its Efficacy in Improving Gait in Patients with Multiple Sclerosis - Sahraian, M.A. (Libertas Academica, 2011)
Multiple sclerosis (MS) is a progressive immune-mediated neurodegenerative disease of human central nervous system (CNS), which causes irreversible disability in young adults. The cause and cure for MS remain unknown. Pathophysiology of MS includes two arms: inflammatory demyelination and neurodegeneration. The inflammatory demyelination of MS which is mainly promoted by a massive activation of the immune system against putative CNS antigen(s) leads to loss of oligodendrocyte/myelin complex which slows down or halts impulse conduction in denuded axons. Practically, loss of myelin significantly reduces signal conduction along the demyelinated axons through alterations in the distribution of axonal ion channels. Dalfampridine (4-aminopyridine or 4-AP) is an oral potassium channel blocker, which was recently approved by FDA for symptomatic treatment of MS. Dalfampridine, which acts at the central and peripheral nervous systems, enhances conduction in demyelinated axons and improves walking ability of MS patients. A number of clinical trials have evaluated the safety and efficacy of fampridine in MS patients with the degree of gait improvement as the main outcome. The objective of this manuscript is to provide an overview of the pharmacology, pharmacokinetics, clinical trials, side effects and interactions of dalfampridine used in treatment of MS patients.